Closing gaps in Open Distance Learning for theology students - E. Oliver (Acta Theologica)
UNISA’s policy documents state clearly that the Open Distance Learning (ODL) concept aims to bridge the time, geographical, economic, social, educational and communication distance between student and institution, student and academics, student and courseware as well as student and peers. Blended learning and student-centredness remove barriers to effective learning, provide flexibility, and construct learning programmes with the expectation that students can succeed. Student-centredness and blended learning are the main drivers behind the intense evaluation and planned upgrading of the courses taught within the Department of Christian Spirituality, Church History and Missiology. The student profile showed that our students are indeed a unique group with diverse interests and expectations from the theological courses for which they enrolled. By adjusting the values of the four components of blended learning and using both active and passive learning tools, students can learn course content and develop a core of applicable, transferable skills needed to succeed in the Open Distance Learning environment.